Anchored Phylogenomics, Evolution and Systematics of Elateridae: Are All Bioluminescent Elateroidea Derived Click Beetles? - Hume B. Douglas; Robin Kundrata; Adam J. Brunke; Hermes E. Escalona; Julie T. Chapados; Jackson Eyres; Robin Richter; Karine Savard; Adam Ślipiński; Duane McKenna; Jeremy R. Dettman (Biology, 2021)
Click-beetles (Coleoptera: Elateridae) are an abundant, diverse, and economically important beetle family that includes bioluminescent species. To date, molecular phylogenies have sampled relatively few taxa and genes, incompletely resolving subfamily level relationships. We present a novel probe set for anchored hybrid enrichment of 2260 single-copy orthologous genes in Elateroidea. Using these probes, we undertook the largest phylogenomic study of Elateroidea to date (99 Elateroidea, including 86 Elateridae, plus 5 non-elateroid outgroups). We sequenced specimens from 88 taxa to test the monophyly of families, subfamilies and tribes. Maximum likelihood and coalescent phylogenetic analyses produced well-resolved topologies. Notably, the included non-elaterid bioluminescent families (Lampyridae + Phengodidae + Rhagophthalmidae) form a clade within the otherwise monophyletic Elateridae, and Sinopyrophoridae may not warrant recognition as a family. All analyses recovered the elaterid subfamilies Elaterinae, Agrypninae, Cardiophorinae, Negastriinae, Pityobiinae, and Tetralobinae as monophyletic. Our results were conflicting on whether the hypnoidines are sister to Dendrometrinae or Cardiophorinae + Negastriinae. Moreover, we show that fossils with the eucnemid-type frons and elongate cylindrical shape may belong to Eucnemidae, Elateridae: Thylacosterninae, ancestral hard-bodied cantharoids or related extinct groups. Proposed taxonomic changes include recognition of Plastocerini as a tribe in Dendrometrinae and Hypnoidinae stat. nov. as a subfamily within Elateridae.